Quantitation of immunoglobulins (IgG, IgM and IgA) in serum and lacteal secretion of buffaloes (Bubalus bubalis) - GOEL, M C; KAKKER, N K (The Indian Journal of Animal Sciences, 2013)
Buffalo immunoglobulins (Igs) IgG1, IgG2 igM and IgA were prepared and monospecific antiserum was raised against each. These were utilized to quantitate Igs in 66 Sera samples and lacteal secretions of 3 buffaloes from 0 to 84 hr postpartum. The concentration of Igs in serum was unaffected by age of the animals and their distribution was normal. The mean IgG11, IgG2, IgG, IgM and IgA concentration in serum was 17.46, 14.08,31.54,2.92 and 0.27 mg/ml, respectively. The corresponding values in lacteal secretions of the 3 buffaloes immediately postpartum were 31.62, 1.96,33.58,0.52 and 0.27 mg/ml, respectively. Thereafter the Ig ,concentrations declined sharply, 7-fold by 24 hr and more than 30-fold by 84 hr postpartum.